Combustion characteristics of methane in a direct injection engine using spark plug fuel injector - Taib Iskandar Mohamad (2010)
The combustion characteristics of methane in a direct injection spark ignition engine using Spark Plug Fuel Injector (SPFI) was investigated. SPFI is a system developed to convert any externally-mixing (port injection, carburetor) spark ignition engine to direct injection by combining fuel injectors into spark plugs. The burning rates of methane were measured using normalized combustion pressure method, where the normalized pressure rise due to combustion is equivalent to the mass fraction burnt at the specific crank angle. A single cylinder research engine was installed with the SPFI system. Cylinder pressures were taken with engine running at 1100 rpm and stoichiometric air/fuel ratio. The spark timing was set at 25oBTDC. For comparison, the engine was run with methane port injection. The optimal fuel injection timing with SPFI was found to be 170o BTDC. Results showed that SPFI direct injection, increased the volumetric efficiency by 11% compared to port injection, resulting in higher heating value of cylinder charge per cycle. Combustion analysis show that the overall burning rate of methane direct injection is faster than the ones of port injection although is slower at the initial stage. Injection pressures affect ignition delay but not the combustion duration. Changing mixture stoichiometry affects the magnitude of ignition delay. Combustion duration increases with leaner mixture. Different load conditions have significant effect on combustion process. Lower loads tend to increase combustion duration but shorten ignition delay. SPFI Di methane system has the potential of increasing engine performance due to increased volumetric efficiency and faster burning rate